Mechanics of 3D printing process of white chocolate - Muhamad Parid, Dzieda; Talib, Ahmad Tarmezee; Baharuddin, Azhari Samsu; Abdul Rahman, Nur Aliaa; Mohammed, Mohd Afandi P.; Wakisaka, Minato (Elsevier Ltd, 2025)
Mechanical and rheological investigation of extrusion-based 3D printing process of white chocolate was conducted in this study by comparing the commercial printer with a syringe/extruder. The extruder mimicked the commercial printer (limited to single axis movement in this study), with the added advantage of recording force-displacement data during printing process through the connection with the texture analyzer. Experimental results showed consistent extrudate output even though there were observations of static zones near the syringe angle. Approximately steady-state extrusion pressure was achieved after 10–20 mm displacement from all tests. On the other hand, die swell decreased with smaller nozzles by the ratio of 42–53 %. Likewise, syringe tip opening/diameter significantly influenced pressure-displacement curves compared to temperature changes of the samples. This work showed that the chocolate temperature of 36 °C facilitated smoother printing process, whereas printing issues like clogging and stacking layers occurred at lower temperatures. Finally, finite element modelling work using axisymmetric elements highlighted the concentration of stress at the vicinity of static zones and die mouth regions.